2020
DOI: 10.1002/pol.20200673
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of a semi‐crystalline diketopyrrolopyrrole‐terthiophene polymer

Abstract: Few semiconducting polymers are known that possess more than one semi‐crystalline structure. Guidelines for rationalizing or creating polymorphism in these materials do not exist. Two different semi‐crystalline polymorphs, β1 and β2, and an amorphous α phase have recently been identified for alternating diketopyrrolopyrrole‐quaterthiophene copolymers (PDPP4T). The polymorphs differ structurally by the π–π stacking distance, and electronically by the optical bandgap and charge carrier mobility. Here we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[20][21][22][23][24][25] As an outstanding representative of D-A conjugated polymers, diketopyrrolopyrrole (DPP)-based conjugated polymers (PDPPs) have won the favor of researchers. 26 Russell et al found that the morphology of PDPP and fullerene blend films changed from large scale heterogeneous structures to fibrous network structure when additives were used. 27 The fibrous network structure was formed through crystallization of PDPP first and then deposition of amorphous PDPP and fullerene.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] As an outstanding representative of D-A conjugated polymers, diketopyrrolopyrrole (DPP)-based conjugated polymers (PDPPs) have won the favor of researchers. 26 Russell et al found that the morphology of PDPP and fullerene blend films changed from large scale heterogeneous structures to fibrous network structure when additives were used. 27 The fibrous network structure was formed through crystallization of PDPP first and then deposition of amorphous PDPP and fullerene.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent Type . The solvent affects not only the solubility of conjugated polymers but also the formation of solution-state aggregates . Generally, the polymer gradually transforms from a coil-like conformation to a globular conformation as the solvent changes from good to bad .…”
mentioning
confidence: 99%
“…The solvent affects not only the solubility of conjugated polymers but also the formation of solution-state aggregates. 44 Generally, the polymer gradually transforms from a coil-like conformation to a globular conformation as the solvent changes from good to bad. 45 Not all polymers can take the shape of collapsed globules as the backbone of a conjugated polymer is rigid or semirigid.…”
mentioning
confidence: 99%